2019
DOI: 10.2460/ajvr.80.9.868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of commonly used α2-adrenergic receptor agonists alone and in combination with butorphanol tartrate on objective measurements of lameness in horses

Abstract: OBJECTIVE To determine the effects of 3 α2-adrenergic receptor agonists (α2-ARAs), alone or in combination with butorphanol tartrate, on objective measurements of lameness in horses. ANIMALS 17 adult polo horses with naturally occurring forelimb or hind limb lameness (or both). PROCEDURES In a crossover design, each horse received each protocol (saline [0.09% NaCl] solution [2 mL, IV] or xylazine hydrochloride [0.33 mg/kg, IV], detomidine hydrochloride [0.007 mg/kg, IV], or romifidine hydrochloride [0.033 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Depth of sedation was objectively assessed using head height, as reported in previous studies 32‐34 . Across both treatment groups, there was a significant effect of time on all variables, regardless of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Depth of sedation was objectively assessed using head height, as reported in previous studies 32‐34 . Across both treatment groups, there was a significant effect of time on all variables, regardless of treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Buchner et al (1999) found that the use of detomidine did not alter forelimb lameness degree but did alter the general locomotory pattern. Likewise, the study by Moorman et al (2019) found no effect of detomidin on head movement asymmetry but did find a significant difference in pelvic movement asymmetry across all data points. They found no significant difference in head or pelvic movement asymmetry when using detomidine combined with butorphanol.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 82%
“…The use of detomidine hydrochloride was studied by Buchner et al (1999) and Moorman et al (2019). Buchner et al (1999) found that the use of detomidine did not alter forelimb lameness degree but did alter the general locomotory pattern.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%
See 2 more Smart Citations